PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER BERBANTUAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 2 BUGBUG - I Made Agus Kartika Putra; I Made Sujana Adnyana (STKIP Subang, 2026)
The main problem addressed in this study is the low academic achievementof fourth-grade students at Bugbug Public Elementary School 2. This study aims toimprove academic achievement using the Numbered Heads Together cooperativelearning model supported by WordWall. This study is a classroom action research(CAR) project. The subjects of this study were 28 fourth-grade students at BugbugPublic Elementary School 2, consisting of 15 boys and 13 girls. The data collectedwere quantitative data using a test instrument to measure learning outcomes. Thelearning outcomes after Cycle I showed an initial average score of 66 and aclassical learning mastery rate of 46%. No significant improvement in learningoutcomes was observed in Cycle I. In Cycle II, an improvement in learning outcomes was evident, with an average score of 78 and a classical learning mastery rate of 93%. Based on the above findings, it can be concluded that the implementation of the Numbered Heads Together cooperative learning model, supported by WordWall, can improve the learning outcomes of fourth-grade students at State Elementary School 2 Bugbug